In-Vitro Evaluation of Water Sorption and Solubility of G-Cem and FujiCem in Water and Acid - Haleh Heshmat; Sepideh Banava; Parisa Zarandi; Foad Faraji (Islamic Dental Association of Iran, 2013)
Background and Aim: Solubility is among the negative characteristics of dental materials leading to structural degradation of cements and decreased longevity of restorations. The present study sought to assess the water sorption and solubility of FujiCem resin-modified glass ionomer (RMGI) and G-Cem self-adhesive resin cement in water and acid .   Materials and Methods : In this experimental study, 5 discs were fabricated from each understudy cement for solubility testing in lactic acid and 5 other disc-shaped specimens were made for evaluation of water sorption and solubility. Specimens were immersed in distilled water for 7 days and immediately weighed afterwards (M2). Discs were then transferred to a desiccator again to reach a constant weight of M3. Water sorption and solubility were calculated using the respective equations. For acid solubility testing, specimens were immersed in lactic acid for 24h. Independent t-test was applied for statistical analysis of results .   Results: Solubility in distilled water was 0.0000139±0.0001μg/m3 for FujiCem and 0.0000016±0.000005μg/m3 for G-Cem (P=0.480). Water sorption was 0.0000197±0.000234 for FujiCem and 0.0000025±0.00004 for G-Cem (P<0.001). Acid solubility was 0.0059414±0.0016 for FujiCem and 0.0039115±0.0016μg/m3 for G-Cem (P=0.348 ).   Conclusion: The two understudy cements had no significant difference in water or acid solubility but FujiCem RMGI showed greater water sorption than G-Cem self-adhesive resin cement .